2013
DOI: 10.1038/srep01572
|View full text |Cite|
|
Sign up to set email alerts
|

CD8+ T cell activation by murine erythroblasts infected with malaria parasites

Abstract: Recent studies show that some human malaria parasite species Plasmodium falciparum and P. vivax parasitize erythroblasts; however, the biological and clinical significance of this is unclear. To investigate further, we generated a rodent malaria parasite (P. yoelii 17XNL) expressing GFP-ovalbumin (OVA). Its infectivity to erythroblasts was confirmed, and parasitized erythroblasts were capable of initiating malaria infections. Experiments showed that MHC class I molecules were highly expressed on parasitized er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 36 publications
5
44
0
Order By: Relevance
“…Moreover, the level of H2 K expression on P. yoelii 17X infected cells from mice of different strains correlates with the ability of each strain to control the infection (Jayawardena et al, 1983). More recently, it has been shown that malaria parasites can parasitize erythroblasts, which have high levels of MHC class I molecules and the capacity to activate CD8+ T cells (Imai et al, 2013). Importantly, H2 K and H2 D molecules were present in exPy (Martin-Jaular et al, 2011) and rexPy (Dataset S3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the level of H2 K expression on P. yoelii 17X infected cells from mice of different strains correlates with the ability of each strain to control the infection (Jayawardena et al, 1983). More recently, it has been shown that malaria parasites can parasitize erythroblasts, which have high levels of MHC class I molecules and the capacity to activate CD8+ T cells (Imai et al, 2013). Importantly, H2 K and H2 D molecules were present in exPy (Martin-Jaular et al, 2011) and rexPy (Dataset S3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evidence has shown that parasitized erythroblast could activate CD8 ϩ T cells (26). Although CD8 ϩ T cells were found to be dispensable for the protective effect of ITV-immunized mice against blood-stage challenge (7), it is protective in the immunized mice that survived infection with both P. yoelii XNL and, subsequently, P. yoelii 17XL (27).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to mature erythrocytes that have completely lost expression of MHC molecules. Previous work using a genetically engineered mouse model of murine malaria has shown that CD8 + T cells can be activated by parasitized erythroblasts but not parasitized mature red blood cells through MHC-I dependent mechanisms [16]. Thus, we hypothesize that the higher proportion of infected reticulocytes in P .…”
Section: Discussionmentioning
confidence: 86%